2013
DOI: 10.1038/jes.2013.9
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected results in a randomized dietary trial to reduce phthalate and bisphenol A exposures

Abstract: Diet is a primary source of exposure for high-molecular-weight phthalates and bisphenol A (BPA), but little is known about the efficacy of various interventions to reduce exposures. We conducted a randomized trial with 10 families to test the efficacy of a 5-day complete dietary replacement (Arm 1; n=21) versus written recommendations to reduce phthalate and BPA exposures (Arm 2; n=19). We measured phthalate and BPA concentrations in urine samples at baseline, intervention, and post-intervention periods. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(120 citation statements)
references
References 34 publications
(41 reference statements)
4
114
2
Order By: Relevance
“…It is worth noting that during the intervention none of the women had dental sealants placed, nor did they change their lifestyle in a way that could have been additional source of BPA exposure. Our results, supported also by other studies, 11,12 are alarming, especially considering the fact that BPA is an environmental estrogen, and it is likely that constant exposure even to low doses may disrupt the action of endogenous hormones.…”
Section: Resultssupporting
confidence: 89%
“…It is worth noting that during the intervention none of the women had dental sealants placed, nor did they change their lifestyle in a way that could have been additional source of BPA exposure. Our results, supported also by other studies, 11,12 are alarming, especially considering the fact that BPA is an environmental estrogen, and it is likely that constant exposure even to low doses may disrupt the action of endogenous hormones.…”
Section: Resultssupporting
confidence: 89%
“…However, it is difficult and impractical to attempt to provide phthalate-free food to participants. Like Sathyanarayana et al (2013), we could easily end up with contaminated food that biases the interpretation of our results. Moreover, as the 2011 Taiwan food scandal demonstrated, finding phthalate-free food may be impossible: five major food categories in Taiwan had been phthalate-tainted for at least two decades (Yen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Rudel et al (2011) conducted a full dietary intervention in five families and found significant reductions in their urinary phthalates when they stopped eating foods prepared or stored in plastic containers. Sathyanarayana et al (2013) tried a complete dietary replacement to reduce exposure to phthalates, but they failed because the replacement food was contaminated with DEHP. They found that written recommendations to prevent dietary contamination caused by plastics were insufficient to help people reduce their exposure to phthalates.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies indicate that diet accounts for more than 90 % of potential BPA exposure in the environment of the general population (50,73) , other studies have found that diet explains a significantly lower proportion of urinary BPA levels (44,47,48,108) . Intervention studies have demonstrated the ability to lower, but not eliminate BPA exposure among study participants (50,59,71,109) . In the current study, only recent canned food intake, as (a) urinary BPA levels compared with reported canned food intake on the BEAM (r = 0·19, P = 0·14); (b) urinary BPA levels compared with reported canned food intake on 24 h food records (r = 0·35, P = 0·004); (c) urinary BPA levels compared with BEAM score (r = 0·26, P = 0·03); (d) urinary BPA levels compared with food record score (r = 0·32, P = 0·008).…”
Section: Discussionmentioning
confidence: 99%
“…However, a more recent study did not observe the expected decrease in urinary BPA levels when packaged foods were removed from study participants' diet (71) .…”
mentioning
confidence: 80%